(untitled) (Journal of the College of Basic Education, 2023)
In this paper I deal with quaternions history which were discovered by William Rowan Hamilton in 1843. Also I take some definitions and the basic properties of quaternions. My basic aim is how to representing quaternions as matrices. There are at least two ways of the representing of matrices, the first way is used 2×2 complex matrices and the second one is used 4×4 real matrices. I can able to generalize the first way by using n×n complex matrices that n is even.